2015
DOI: 10.3368/aoj.65.1.99
|View full text |Cite
|
Sign up to set email alerts
|

Is The Convergence Insufficiency Symptom Survey Specific for Convergence Insufficiency? A Prospective, Randomized Study

Abstract: CISS scores tend to be higher when self-vs. practitioner-administered. This study suggests that the CISS questionnaire is not specific for convergence insufficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 5 publications
1
7
0
Order By: Relevance
“…Our CISS VE showed a mean score (15.10 ± 10.13) that was comparable to those reported in studies conducted in similar populations, such as the adolescents assessed by Horan et al 6 (16.3 ± 11.4) and the university students used to develop the Portuguese version (CISS VP ; 15.56 ± 8.86). 5 These two studies provided mean scores for the entire group of participants instead of separating scores according to subjects' visual problems.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Our CISS VE showed a mean score (15.10 ± 10.13) that was comparable to those reported in studies conducted in similar populations, such as the adolescents assessed by Horan et al 6 (16.3 ± 11.4) and the university students used to develop the Portuguese version (CISS VP ; 15.56 ± 8.86). 5 These two studies provided mean scores for the entire group of participants instead of separating scores according to subjects' visual problems.…”
Section: Discussionsupporting
confidence: 87%
“…Accordingly, it considers the most common symptoms regarding near-vision problems 5 and provides similar scores in children with accommodative insufficiency and convergence insufficiency. 4 In addition, as described by Horan et al, 6 some patients with normal sensorimotor exam results were found to score high (i.e., showed a higher level of the assessed symptoms) on the CISS, while others with convergence insufficiency had relatively low scores.…”
Section: Introductionmentioning
confidence: 81%
“…Forty five per cent of included OMDs studies [81–116] had adults exclusively as subjects due to the nature of conditions under evaluation such as thyroid eye disease and neurological diseases with gaze palsies, which exist in adults typically. In contrast, less than tenth of the studies were done on paediatric subjects [117–124]. Some of these were for conditions found predominantly in teenagers such as convergence insufficiency and accommodation dysfunction and others included disorders with an early onset such as infantile nystagmus and pattern deviations.…”
Section: Resultsmentioning
confidence: 99%
“…“Near point of convergence NPC” and “positive fusional vergence” were less common. Alignment measurement was not expansively assessed in included studies apart from measuring “phoria” in two studies [128, 147] or ruling out manifest strabismus with “cover test at distance and near” for inclusion in one trial [124] . “ Amplitude of accommodation” [118, 128, 147], and “accommodative facility” [118, 147] were also reported.…”
Section: Resultsmentioning
confidence: 99%
“…Although some reports indicate a low specificity for CISS scores, they are still used for the subjective evaluation of patients with CI. [ 15 16 17 ]…”
Section: Methodsmentioning
confidence: 99%